Phytochemicals and Cytotoxicity of Quercus infectoria Ethyl Acetate Extracts on Human Cancer Cells - Wan Nur Suzilla Wan Yusof,; Hasmah Abdullah, (Tropical Life Sciences Research, 2020)
Conventional and modern cancer treatment were reported to manifest adverse effects to the patients. More researches were conducted to search for selective cytotoxic agent of plant natural product on cancer cells. The presences of wide range phytochemicals in Quercus infectoria (QI) extract have been implicated with the cytotoxic effect against various types of cancer cell which remain undiscovered. This present study aimed to evaluate cytotoxic effect of QI extracts on selected human cancer cells and then, the most potent extract was further analysed for general phytochemical constituents. QI galls were extracted successively with n-hexane, ethyl acetate and methanol yielded three main extracts; n-hexane (QIH), ethyl acetate (QIEA) and methanol (QIM), respectively. The most potent extract was qualitatively analysed for the present of tannin, alkaloids, glycosides, saponins, terpenoids, flavonoids and phenolic compounds. Next, the extracts were tested to determine the cytotoxic activity against cervical cancer cells (HeLa), breast cancer cells (MDA-MB-231) and liver cancer cells (HepG-2) using MTT assay. Cytotoxic activity of QI extracts against normal fibroblast (L929) cell line was also evaluated to determine the cytoselective property. Meanwhile, DMSO-treated cells served as negative control while cisplatin-treated cells served as positive control. The most potent extract then chosen to be further investigated for DNA fragmentation as hallmark of apoptosis using Hoechst staining. Qualitative phytochemical analysis revealed the presence of tannin, alkaloids, glycosides, saponins, terpenoids, flavonoids and phenolic compounds. QIEA extract exhibited the most potent cytotoxic activity against HeLa cells with (IC50 value = 6.33 ± 0.33 ?g/mL) and showed cytoselective property against L929 cells. DNA fragmentation revealed QIEA induced apoptosis in the treated cells. The richness of phytochemical constituents in QIEA extract might contribute to the potency of cytotoxic activity towards HeLa cells.